2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6186660
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency on boron emitter n-type Cz silicon solar cells with industrial process

Abstract: The fabrication of n-type solar cell using industrial process is presented in this study. The boron emitter was formed using novel diffusion technique with BCl 3 precursor and the passivation was made by means of dry oxidation. The influence of the grid coverage ratio on the backside was studied and an optimized value of 5% was found. Efficiencies above 19.0% were obtained on 125PSQ Cz wafers. We also report a independently certified efficiency of 18.7% measured by Callab on a special bifacial chuck. A differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Many former challenges, such as the formation of p + (boron) emitters and passivation thereof are basically overcome. However, recent studies have shown that the metallization using screen printing and firing through technique still limits the open‒circuit voltage ( V O C ) of such cell types . The already industrially proven metallization for the n + emitters by using screen‒printed Ag pastes does not successfully work also for the p + diffused emitters, due to very high contact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Many former challenges, such as the formation of p + (boron) emitters and passivation thereof are basically overcome. However, recent studies have shown that the metallization using screen printing and firing through technique still limits the open‒circuit voltage ( V O C ) of such cell types . The already industrially proven metallization for the n + emitters by using screen‒printed Ag pastes does not successfully work also for the p + diffused emitters, due to very high contact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation highlighted up to now is the high number of process steps compared to the simple p‐type solar cell process. Indeed, using conventional BBr 3 and POCl 3 high temperature diffusions, several masking steps and chemical oxide removal must be added in order to isolate the front B‐emitter from the rear P‐BSF . Among the various ways discussed in the literature to simplify this process flow, two solutions have been highlighted: the co‐diffusion approach and the use of ion implantation .…”
Section: Introductionmentioning
confidence: 99%
“…The fire‐through Ag/Al paste could damage the emitter junction area and lower the V oc of the solar cells . In order to decrease the emitter contacts losses, we design a new type of floating bus bar configuration and compare with the regular bus bar.…”
Section: Resultsmentioning
confidence: 99%